Performance analysis of MPPM FSO transmission over Gamma–Chi-square strong atmospheric turbulence - Todorovic, Jelena; Spalevic, Petar; Panic, Stefan; Abdullah, Majid Hamid; Pantelic, Ivan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
In this paper, performance analysis of free space optical (FSO) system operating in conditions of strong atmospheric turbulence over Gamma–Chi-square turbulence model, has been carried out. We have observed reception over multi-pulse pulse-position (MPPM) modulation format for the case of strong atmospheric turbulence conditions modeled with Gamma–Chi-square turbulence model and have compared it with turbulence modeling distributions such are: Gamma–Gamma distribution, K-distribution, negative exponential distribution, log–normal distribution. First, we have provided closed-form analytical expressions for average bit error rate (ABER) at the reception for each observed case and then based on them, we have obtained numerical and Monte Carlo simulation results in order to observe turbulence level impact on system performance.
Optica Applicata, Vol. 53, 2023, nr 1, s. 111-126
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; FSO – free space optical; ABER – average bit error rate; MPPM – multi-pulse pulse-position; novel Gamma–Chi-square distribution; channel model; strong atmospheric turbulence